A traumatic hepatic artery pseudoaneurysm and arterioportal fistula, with severe diarrhea as the first symptom: A case report and review of the literature. Issue 7 (February 2018) - Han, Ping; Yang, Lan; Huang, Xiao-Wei; Zhu, Xiu-Qin; Chen, Li; Wang, Nan; Li, Zhen; Tian, De-An; Qin, Hua
Abstract: Rationale: Hepaticarterioportal fistula (APF) is a rare cause of portal hypertension and gastrointestinal hemorrhage, and presents as abnormal communication between the hepatic artery and portal vein. Percutaneous liver biopsy is a main iatrogenic cause of AFP. However, non-iatrogenic, abdominal, trauma-related APF is rarely reported. Patient concerns: A 29-year-old man presenting with severe, watery diarrhea was transferred to our hospital, and his condition was suspected to be acute gastroenteritis because he ate expired food and suffered a penetrating abdominal stab wound 5 years ago. After admission, the patient suffered from hematemesis, hematochezia, ascites, anuria, and kidney failure, and he developed shock. Diagnoses: The patient was finally diagnosed as a traumatic hepatic artery pseudoaneurysm and APF. Interventions: This patient was treated with emergency transarterial embolization using coils. Since a secondary feeding vessel was exposed after the first embolization of the main feeding artery, a less-selective embolization was performed again. Outcomes: During the 6-month follow-up period, the patient remained asymptomatic. Lessons: A penetrating abdominal stab wound is a rare cause of hepatic APFs, and occasionally leads to portal hypertension, the medical history and physical examination are the most important cornerstones of clinical diagnosis. Interventional radiology is essential for the diagnosis and treatment of an APF.